2022
DOI: 10.1111/ejh.13803
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of adult primary immune thrombocytopenia in England—An update

Abstract: Background Adult primary immune thrombocytopenia (ITP) is a rare bleeding disorder of unknown cause. Recent estimates of its incidence and trend over time were acquired for England. Method The primary ITP population (using ICD 10 code D693 and excluding secondary ITP cases; positive predictive value: 82.6%) was sourced from NHS Digital inpatient and outpatient. Incidence rate (IR) for England and by age groups, sex, and regions were calculated and trends were assessed using average annual percent change (AAPC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
1
6
0
4
Order By: Relevance
“…In recent years, there seems to be a trend toward a higher age at onset (∼60 years). Almost one-third of patients are more than 70 years old [4,5].…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there seems to be a trend toward a higher age at onset (∼60 years). Almost one-third of patients are more than 70 years old [4,5].…”
Section: Epidemiologymentioning
confidence: 99%
“…Differential diagnosis of thrombocytopenia in pregnancy. 1 EDTA, ethylenediaminetetra-acetic acid; 2 GT, gestational thrombocytopenia; 3 ITP, immune thrombocytopenia; 4 HIV, human immunodeficiency virus; 5 HELLP syndrome (hemolytic anemia, elevated liver enzymes, low platelets); 6 TTP, thrombotic thrombocytopenic purpura; 7 HIT, heparin-induced thrombocytopenia; 8 E.g., myelodysplastic syndrome, myeloproliferative neoplasms.…”
Section: Older Patients Patients With Comorbidities Thrombosis and An...mentioning
confidence: 99%
“…Several large epidemiological studies have shown that the ITP epidemiology is influenced by sex and age, 2 , 3 , 6 with peaks in young women and old men. ITP is also a geriatric disease, with incidence rates reaching 23.9/100 000 in men >80 years old in the United Kingdom 3 and 9/100 000 person-years in men >75 years old in France, 2 that is, an approximately 10-fold increase as compared with men aged 30 to 39 years in both studies. In a recent French study including 541 adults with incident ITP included in a prospective national registry, 251 (46%) were ≥65 years and among them, 47% were ≥80 years.…”
Section: Itp Diagnosis and Epidemiologymentioning
confidence: 99%
“… 1 Although it can affect individuals of all age categories, the disease incidence peaks in older patients. 2 , 3 Hence, combined with the worldwide trend in the ageing of the population, ITP is of particular interest for physicians taking care of older patients. ITP management is challenging in older versus younger patients given the frequent comorbidities and increased risk of bleeding, infections and thrombosis of the former group.…”
Section: Introductionmentioning
confidence: 99%
“…In den letzten Jahren scheint es einen Trend zu einem höheren Erkrankungsalter zu geben (um die 60 Jahre). Fast 1/3 der Patient*innen sind über 70 Jahre alt [4,5].…”
Section: Epidemiologieunclassified